Education, Health and Fertility of UK Immigrants: The Role of English Language Skills - Yu Aoki; Lualhati Santiago (Institute for the Study of Labor (IZA), 2015)
This paper aims to identify the causal effect of English language skills on education, health and fertility outcomes of immigrants in England and Wales. We construct an instrument for language skills using age at arrival in the United Kingdom, exploiting the fact that young children learn languages more easily than older children and adults. Using a unique individual-level dataset that links 2011 census data to life event records for the population living in England and Wales, we find that better English language skills significantly lower the probability of having no qualifications and raise that of obtaining academic degrees, but do not affect child health and self-reported adult health. The impact of language on fertility outcomes is also considerable: Better English skills significantly delay the age at which a woman has her first child, lower the likelihood of becoming a teenage mother, and decrease fertility.
Keywords: I10; I20; J13; 330; language skills; education; health; fertility